PENGARUH PEMBERDAYAAN KARYAWAN, KOMITMEN ORGANISASIONAL DAN KOMPENSASI FINANSIAL TERHADAP KEPUASAN KERJA KARYAWAN - Dewi, I Gusti Agung Surya; Suwandana, I Gusti Made (E-Jurnal Manajemen; Vol 5 No 4 (2016), 2016)
This research was done on the LPD Jimbaran, using all of its employees as respondents who totaled 82 people with saturated sample method. Design penelitiaan used this research is Quantitative Research and is associative kausalitas. Analysis Technic used in this research is multiple linear regression. Employee empowerment and significant positive effect on job satisfaction. This means that the more employees feel empowered by the organization, the level of employee satisfaction will increase. Organizational commitment and significant positive effect on job satisfaction. This means that the larger organizational commitment owned by an employee, the employee satisfaction level will increase. Financial compensation and significant positive effect on job satisfaction. This means that the higher the financial compensation granted to employees, the higher the level of employee satisfaction
Keywords: Employee empowerment, organizational commitment, financial compensation, and job satisfaction